Pengembangan Sistem Portal Satu Data Indonesia Pada Kantor Staf Presiden Menggunakan Comprehensive Kerbal Archieve Network (CKAN) - Bayu Wicaksono; Denny Sagita Rusdianto; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Data is a valuable national resources and strategic asset for Government and society in Indonesia. Manage data as an assets and make it available, can be found and used for encourage government's openness, efficiency and effectivity. So far, data become less attention from instance, so it needs some research to do data integration between more than two different platform using comprehensive kerbal archive network (CKAN). To be able to do data integration, there's some method the usage is based on the availability of metadata source and through application programming interface (API) CKAN. Data Harvesting are divided into three steps, the first step is collecting metadata source to be taken through API CKAN. The second step is take the metadata from related source and save it into database. The last step is input metadata into dataset. The purpose of this research is to do integration between CKAN system. This system has been successfully tested using white box testing method on unit testing and integration testing, also black box testing on validation testing. Testing data synchronization is done with percentage of success above 90%, where the test is done by using 2 samples on Bandung data portal and National data portal. Bandung data portal shows successful data taken as much as 100% and the National data portal is 99.87%.